Interest rates and business cycles in emerging economies: the role of financial frictions - Andrés Fernández; Adam Gulan (Bank of Finland, 2012)
Countercyclical country interest rates have been shown to be both a distinctive characteristic and an important driving force of business cycles in emerging market economies. In order to account for this, most business cycle models of emerging market economies have relied on ad hoc and exogenous countercyclical interest rate processes. We embed a financial contract àla Bernanke et al. (1999) into a standard small open economy business cycle model that endogenously delivers countercyclical interest rates. We then take the model to the data. For this purpose we build a novel panel dataset for emerging economies that includes financial data, namely sovereign and corporate interest rates as well as leverage. We show that the model accounts well not only for countercyclical interest rates, but also for other stylized facts of emerging economies' business cycles, including the dynamics of leverage.
URN:NBN:fi:bof-20140807392
Keywords: 330